Clinical, laboratorial and surgical aspects of 15 cases of pyometra in bitches (Research, Society and Development, 2021)
Pyometra is a disease characterized by an supurative infection in the uterus, it is a disease that has hormones influence and can occur at any phase of the estrous cycle, but has a bigger predisposition in the diestrous. The objective of this paper was na comparative study between fifteen medical records of bitches diagnosed with pyometra. The epidemiologic datas such as breed, size, age, medical history, clinical sings, complementary exams, pyometra type and treatment of choice were colected and rated. In this study closed pyometra was the predominant type. The most prevalente clinical signs were anorexia, prostration and vulvar secretion. It is important to highligt that the blood and images exams were done to clarify each case and the ovariohisterectomy was the treatment of choice.